2001
DOI: 10.1128/jcm.39.11.3942-3945.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antimicrobial Susceptibility of Alcaligenes xylosoxidans Isolated from Patients with Cystic Fibrosis

Abstract: In the past decade, potential pathogens, including Alcaligenes species, have been increasingly recovered from cystic fibrosis (CF) patients. Accurate identification of multiply antibiotic-resistant gram-negative bacilli is critical to understanding the epidemiology and clinical implications of emerging pathogens in CF. We examined the frequency of correct identification of Alcaligenes spp. by microbiology laboratories affiliated with American CF patient care centers. Selective media, an exotoxin A probe for Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 23 publications
5
88
1
Order By: Relevance
“…Owing to the diversity of colonial morphologies and biochemical reactivity encountered, misdiagnosis of Gram-negative nonfermenters cultured from CF sputum may occur. In one study, misidentification of 11% of A. xylosoxidans strains was reported [30].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the diversity of colonial morphologies and biochemical reactivity encountered, misdiagnosis of Gram-negative nonfermenters cultured from CF sputum may occur. In one study, misidentification of 11% of A. xylosoxidans strains was reported [30].…”
Section: Resultsmentioning
confidence: 99%
“…A. xylosoxidans was misidentified in up to 11% of cases, according to one study (33). When misdiagnosed, A. xylosoxidans is most often falsely identified as nonpigmented strains of Pseudomonas aeruginosa or B. cepacia (34). In light of this propensity for misidentification, sequencing offers a more reliable method of definitive diagnosis (19).…”
Section: Case Reportmentioning
confidence: 99%
“…Pulmonary cases of A. xylosoxidans infection have been associated with a myriad of underlying medical problems, including IgM deficiency (11), hematologic malignancies, including acute myelogenous leukemia (AML) (18,34), solid organ malignancies (20,39), COPD (12), and CF (10, 13, 39, 44) ( Table 1). In one study, A. xylosoxidans was the most common Gram-negative nonfermenter in CF patients, second only to Pseudomonas aeruginosa (13).…”
Section: Case Reportmentioning
confidence: 99%
“…We found very variable results for ceftazidime, while for only one strain (B other) no large inhibition zone for piperacillin was observed. Also, Saiman et al (20) found piperacillin among the most active antibiotics in vitro. There were no consistent susceptibility characteristics which enabled one to differentiate between the four genotypes, but the susceptibility pattern, i.e., colimycin resistance and combined resistance to aminoglycosides and quinolones, was considered to be helpful in distinguishing this species from P. aeruginosa.…”
mentioning
confidence: 99%
“…Due to the diversity of colonial morphologies and biochemical reactivity encountered, misdiagnosis of gram-negative nonfermenters cultured from CF sputum may occur. In one study, misidentification of 11% of A. xylosoxidans strains was reported (20).…”
mentioning
confidence: 99%